1977
DOI: 10.1007/bf00492367
|View full text |Cite
|
Sign up to set email alerts
|

Negative naloxone effects in schizophrenic patients

Abstract: On the basis of the hypothesis that the opiate-like neuropeptides, such as beta-endorphin, may be involved in the etiology of schizophrenic symptoms, naloxone 1,2 mg and placebo were administered intravenously to 8 schizophrenic patients, using a double-blind, crossover design. Naloxone was not found to be different from placebo in effecting schizophrenic symptoms, including hallucinations and delusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Our immunohistochemical studies have shown that (5-endorphin is located in the intermediate and anterior lobes of the pituitary ), in the same cells known to secrete ACTH. This suggestion was supported by reports in which naloxone, a morphine and endorphin antagonist, was found to reduce auditory hallucinations in some schizophrenic patients (Gunne et al 1977), but not in all (Janowsky et al 1977). 31.000), secreted by pitu¬ itary cells (Mains et al 1977) and that ACTH and ß-endorphin are re¬ leased concomitantly in response to stress, adrenalectomy or steroid treatment .…”
Section: Introductory Remarksmentioning
confidence: 75%
“…Our immunohistochemical studies have shown that (5-endorphin is located in the intermediate and anterior lobes of the pituitary ), in the same cells known to secrete ACTH. This suggestion was supported by reports in which naloxone, a morphine and endorphin antagonist, was found to reduce auditory hallucinations in some schizophrenic patients (Gunne et al 1977), but not in all (Janowsky et al 1977). 31.000), secreted by pitu¬ itary cells (Mains et al 1977) and that ACTH and ß-endorphin are re¬ leased concomitantly in response to stress, adrenalectomy or steroid treatment .…”
Section: Introductory Remarksmentioning
confidence: 75%
“…This resulted in 27 publications detailing 30 blinded placebo-controlled trials for our final analysis comprising 434 total patients. Of these 30 trials, one utilized nalmefene [ 87 ] and one utilized buprenorphine [ 88 ], resulting in 28 trials that utilized naloxone or naltrexone [ 8 , 22 , 64 – 67 , 70 72 , 84 , 86 , 89 – 102 ]. The characteristics of included participants are reported in Supplementary Table S6 .…”
Section: Resultsmentioning
confidence: 99%
“…B-endorphin in doses of 1.5-9 mg was reported to benefit three of four schizophrenics in an uncontrolled study [Kline et al, 19771. However, controlled studies found B-endorphin to produce little or no effect [Gerner et al, 1980;Pickard et al, 19811. There is also controversial evidence that naloxone and naltrexone may have a slight effect on auditory hallucinations in some schizophrenic patients [Janowsky et al, 1977;Pickar et al, 19821 as well as thought disorder [Kleinman et al, 19821 Positive results have mainly been found in neuroleptic-treated patients. However, controlled studies with the long-acting opiate antagonist, naltrexone, have been negative, even in neuroleptic-treated schizophrenics [Gitlin et al, 19811. There have been numerous studies of the antipsychotic efficacy of (des-tyr)-gammaendorphin (DTGE) in schizophrenia.…”
Section: Endorphins and Opiate Antagonistsmentioning
confidence: 99%